2006
DOI: 10.1016/j.icesjms.2005.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology and abundance of the white-dotted skate, Bathyraja albomaculata, in the Southwest Atlantic

Abstract: Size at maturity, sexual dimorphism, gonad development, and abundance of white-dotted skate, Bathyraja albomaculata, were assessed along its geographic range in the Southwest Atlantic, from Uruguay to Tierra del Fuego (Argentina). In all, 291 specimens from eight research cruises conducted between 1998 and 2003 were examined. Length–mass relationships were sexually dimorphic, adult females being significantly heavier than males of the same length. The largest female observed was 762 mm total length (LT), and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
0
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 35 publications
6
57
0
10
Order By: Relevance
“…The number of rows of alar thorns in males of S. bonapartii varied between 1 and 6, in agreement with data reported by Mabragaña et al (2002), and also similar to the pattern observed in A. cyclophora (Oddone & Vooren, 2005) and Bathyraja albomaculata (Ruocco et al, 2006). This sexual character present in males can vary among species, being an important parameter used for maturity staging.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The number of rows of alar thorns in males of S. bonapartii varied between 1 and 6, in agreement with data reported by Mabragaña et al (2002), and also similar to the pattern observed in A. cyclophora (Oddone & Vooren, 2005) and Bathyraja albomaculata (Ruocco et al, 2006). This sexual character present in males can vary among species, being an important parameter used for maturity staging.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies have also demonstrated a similarity in this number of maximum of rows of alar thorns, for other species of the same family (Mabragaña et al, 2002;Oddone & Vooren, 2005;Ruocco et al, 2006).…”
Section: Discussionsupporting
confidence: 54%
“…In addition, the higher values in the female GSI observed in December, might be explained by a peak of reproductive activity in spring season, as was proposed by Oddone et al (2008) Mabragaña et al, 2002); A. castelnaui (according to Collonelo et al, 2012); Rioraja agassizi (Müller & Henle, 1841) (according to Colonello et al, 2007a;], where temperatures and photoperiod may affect egg laying rate (Colonello, 2009). The lack of reproductive seasonality is common in deeper waters with less environmental variability, as was observed in B. albomaculata (Norman, 1937) (according to Ruocco et al, 2006), therefore, due to the predominant geographical location of A. cyclophora within the study area (outer coastal shelf, 28.9 -49.6 m bottom depth, 10.6 -14.9ºC mean bottom temperature, Jaureguizar et al, 2006), a mixed coastal-deep reproductive pattern might be possible. On the other hand, the reproductive activity in A. cyclophora males analyzed in this work was continuous through the year, evidenced by the 9 e170098 [9] lack of variation in the GSI between seasons.…”
Section: Discussionmentioning
confidence: 69%
“…But Ebert et al did not reveal significantly difference of this species [16] . The difference between sexes was found for several skates [17,18] . Females reach larger body sizes than males as a consequence of body space needed for egg production and storage during the reproductive stage [18] .…”
Section: Discussionmentioning
confidence: 93%